Analisis Pengaruh Variasi Laju Penimbunan terhadap Deformasi Lateral Tanah Lunak pada Metode Preloading dengan PVD (Studi Kasus Jalan Tol Pekanbaru–Padang STA 10+400) - Dini Oktavia; Dian Purnamawati Solin; Bagas Aryaseta (AGREGAT, 2026)
Construction of embankments on soft soil often encounters stability issues due to low shear strength and high compressibility, particularly when the loading rate is not properly controlled. This study aims to analyze the effect of embankment loading rate on lateral deformation behavior of soft soil improved using preloading combined with Prefabricated Vertical Drains (PVD). The research is based on a case study of the Pekanbaru–Padang Toll Road STA 10+400. The methodology involves numerical analysis using the Finite Element Method (FEM), preceded by manual calculations to determine staged loading scenarios with target degrees of consolidation. Three loading rates were evaluated, namely 0,2; 0,3 and 0,4 m/week. The analysis focuses on settlement, safety factor, and lateral deformation. The results indicate that all loading rate variations produce similar final settlements (approximately 3,7 m) and meet the required degree of consolidation. However, significant differences are observed in lateral deformation and stability. Lower loading rates result in smaller lateral deformation and higher safety factors, indicating improved stability performance. Conversely, higher loading rates generate greater excess pore water pressure, leading to increased lateral deformation and reduced stability margins. It can be concluded that controlling the loading rate plays a critical role in minimizing lateral deformation and ensuring embankment stability on soft soil. A lower loading rate is more effective in providing sufficient time for consolidation and strength gain, thereby improving overall performance.